Did the acute impact of the COVID-19 pandemic on drinking or nicotine use persist? Evidence from a cohort of emerging adults followed for up to nine years. (August 2022) - Pelham, William E.; Yuksel, Dilara; Tapert, Susan F.; Baker, Fiona C.; Pohl, Kilian M.; Thompson, Wesley K.; Podhajsky, Simon; Reuter, Chase; Zhao, Qingyu; Eberson-Shumate, Sonja C.; Clark, Duncan B.; Goldston, David B.; et al.
Highlights: Advent of the COVID-19 pandemic was associated with changes in alcohol use. In June and December 2020, fewer young adults were drinking vs. pre-pandemic. In June 2020, those who drank were drinking on more days vs. pre-pandemic. By June 2021, alcohol use was no longer distinguishable from pre-pandemic patterns. Pandemic impacts on nicotine use were greater among those experiencing financial impact. Abstract: Objective: This study examined the impact of the COVID-19 pandemic on drinking and nicotine use through June of 2021 in a community-based sample of young adults. Method: Data were from 348 individuals (49% female) enrolled in a long-term longitudinal study with an accelerated longitudinal design: the National Consortium on Alcohol and Neurodevelopment in Adolescence (NCANDA) Study. Individuals completed pre-pandemic assessments biannually from 2016 to early 2020, then completed up to three web-based, during-pandemic surveys in June 2020, December 2020, and June 2021. Assessments when individuals were 18.8–22.4 years old ( N  = 1, 458) were used to compare drinking and nicotine use pre-pandemic vs. at each of the three during-pandemic timepoints, adjusting for the age-related increases expected over time. Results: Compared to pre-pandemic, participants were less likely to report past-month drinking in June or December 2020, but there was an increase in drinking days among drinkers in June 2020. By June 2021, both the prevalence of past-month drinking and number of drinking days among drinks were similar to pre-pandemic levels. On average, there were no statistically significant differences between pre-pandemic and during-pandemic time points for binge drinking, typical drinking quantity, or nicotine use. Young adults who reported an adverse financial impact of the pandemic showed increased nicotine use while their peers showed stable or decreased nicotine use. Conclusion: Initial effects of the pandemic on alcohol use faded by June 2021, and on average there was little effect of the pandemic on nicotine use.